Control, with organic matter, of cucumber damping-off caused by Pythium ultimum Trow - Bettiol, Wagner; Migheli, Quirico; Garibaldi, Angelo (Pesquisa Agropecuaria Brasileira, 1997)
The effectiveness of several media [soil-sand-perlite (1:1:1 v/v); soil-sand-perlite-manurc (1:1:1:3); soil-sand-perlite-compost (1:1:1:3); soil-sand-perlite-peat (1:1:1:3); soil-sand-perlite-wheat straw (1:1:1:3), and sand-perlite-peat-compost-manure-wheat straw (2:2:1:3:3:1)] as suppressers of the cucumber (Cucumis sativus L.) dampingoff causal agent, Pythium ultimum Trow., was evaluated. The media were infested with 12 g/L of Pythium inoculum (broken corn-sand medium), fifteen days before sowing ten cucumber seeds (Mezzolungo Marketer) I cm deep in pots containing 500 ml of medium. Plants were grown at a constant temperature of 250C ± 2 with 12 hours of illumination per day. The percentage of emerged seedlings and post- and pre-emergent damping-off and disease severity were determined fifteen days after planting. This procedure was repeated on the same substrate, without inoculation, ten days after harvesting this first trial. The manure medium was the most suppressive to the disease, with percent of emergence and percent of pre- and post-emergence damping-off and disease severity values of 84.5%, 12.0%, 0% and 1.35, respectively, for the first bioassay. The replanting experiment results were 98.5%, 0.0%, 0.0% and 1.0, respectively. Peat medium and the mixture sand-peat-manure-compost-wheat straw medium were more conducive to the disease than wheat straw medium, resulting in higher occurrence and severity of attack by Pythium.
Keywords: suppressiveness; Cucumis sativus; biological control